Factors influencing perseverance in teaching Chinese martial arts abroad: a self-determination theory perspective among international instructors - Cao, Xueying; Lyu, Hui (Frontiers in Psychology, 2024)
Background The global dissemination of Chinese martial arts (CMAs), transcends mere physical activity; it represents a cultural and philosophical journey that contributes to enhanced psychological well-being. Capturing international attention, CMAs have engendered a network of global instructors committed to their cross-cultural teaching. However, the narrative of CMAs across the globe is incomplete without understanding the psychological factors that fuel the perseverance of these international instructors. Their relentless commitment, motivated by factors beyond the cultural and geographical barriers, poses a unique question: What motivates these instructors to persist in teaching CMAs in the face of such challenges? The study aims to uncover the key motivational mechanisms that influence the perseverance of international CMAs instructors in their teaching endeavors. Methods Employing Self-Determination Theory, 147 international CMAs instructors completed the Motivation for Teaching CMAs Scale, Perceived Belonging Scale, and Perseverance in Teaching CMAs Scale. SPSS 20.0 was utilized for conducting descriptive statistics, common method bias tests, and correlation analyses. Structural equation modeling was performed using AMOS 26.0. Results Autonomous Motivation positively affected perseverance in teaching CMAs (β = 0.369, b = 0.465, t = 4.232, p < 0.001). In contrast, Amotivation negatively affected perseverance (β = −0.323, b = −0.382, t = −3.561, p < 0.001). Neither Controlled Motivation nor Sense of Belonging significantly affected perseverance. The model explained 27.9% of the variance in perseverance, offering insights into the motivational mechanisms influencing international CMAs instructors. Conclusion This study concludes that the perseverance of international instructors in teaching CMAs is primarily driven by overcoming amotivation and fostering autonomous motivation, rather than short-term internal or external incentives, which appear ineffective. Additionally, sense of belonging to their CMA school does not significantly influence their perseverance, potentially due to the diverse cultural backgrounds of the instructors surveyed. The findings suggest that by enhancing the recognition and acceptance of CMAs’ core philosophies and values, aligning teaching practices with personal and cultural values, and fostering a profound passion for CMAs, international instructors could boost their autonomous motivation, which is crucial for their sustained commitment in promoting CMAs globally.